2020
DOI: 10.3390/w13010030
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hourly Flood Hydrograph from Daily Flows Using Artificial Neural Network and Flow Disaggregation Technique

Abstract: Flood data on a high temporal scale are required for the design of hydraulic structures, flood risk assessment, flood protection, and reservoir operations. Such flood data are typically generated using rainfall-runoff models through an accurate calibration process. The data also can be estimated using a simple relationship between the daily and the sub-daily flow records as an alternative to rainfall–runoff modelling. In this study, we propose an approach combining an artificial neural network (ANN) model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…They indicated that GRNN is capable of yielding satisfactory outputs. Other scholars have reported similar results [33,34]. However, the previous studies focus mostly on the application of runoff forecasting by GRNN without considering its combination with hydrological modeling software such as SWMM.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…They indicated that GRNN is capable of yielding satisfactory outputs. Other scholars have reported similar results [33,34]. However, the previous studies focus mostly on the application of runoff forecasting by GRNN without considering its combination with hydrological modeling software such as SWMM.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, an ANN known as the general regression neural network (GRNN) has shown promise owing to its rapid calculation speed and good nonlinear approximation performance [28,29]. Therefore, it is widely used in many academic fields, including hydrology [31][32][33][34]. Apaydin et al [31] simulated the daily streamflow to the Ermenek hydroelectric dam reservoir using deep recurrent neural network architectures and reported highly accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution flood event data play a crucial role in various aspects, including the design of hydraulic structures, flood frequency analysis, flood risk assessment, and reservoir operations (Lee, J et al, 2021). For hydraulic design and risk assessments, it is necessary to determine design flood estimates for a specific return period in both gauged and ungauged catchments.…”
Section: Theoretical Frame Workmentioning
confidence: 99%
“…In order to achieve simulation predictions of water quality response within a certain period after the implementation of emission control schemes, we have applied deep learning techniques to the water environment model. Deep learning is a type of data-driven model that has been proven to be a valuable tool in various applications (Lee et al, 2020). For example, it was initially applied to speech-to-text conversion, machine translation, and sequence data processing.…”
Section: Introductionmentioning
confidence: 99%